2011
DOI: 10.1007/s11060-011-0635-0
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife radiosurgery for cranial neurocytomas

Abstract: Gamma-knife surgery may be an effective alternative for treatment of central neurocytomas owing to its relative safety compared with conventional radiotherapy. In this paper we present results of gamma-knife treatment (GKS) of residual or recurrent neurocytomas. Twenty-two patients (14 female, 8 male) with recurrent or residual neurocytomas who underwent GKS were included. Diagnosis was based on histological findings. The proliferative potential of the tumors was examined by immunostaining with MIB-1 antibody,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 50 publications
0
40
0
5
Order By: Relevance
“…Although there is no such comparison for the surgery and radiation, there is a trend showing that post-operative radiotherapy benefits the outcome, as suggested by Jackson et al (10). Genc et al reported 2 cases of cerebellar liponeurocytoma with post-surgery γ-knife therapy, and observed that the tumors diminished in size after a follow-up time of 12 and 53 months, respectively (11). However, certain studies believe that since the recurrence of the tumor occurs in the long term, adjuvant radiation is too aggressive following the initial gross total resection (2)(3)(4)9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no such comparison for the surgery and radiation, there is a trend showing that post-operative radiotherapy benefits the outcome, as suggested by Jackson et al (10). Genc et al reported 2 cases of cerebellar liponeurocytoma with post-surgery γ-knife therapy, and observed that the tumors diminished in size after a follow-up time of 12 and 53 months, respectively (11). However, certain studies believe that since the recurrence of the tumor occurs in the long term, adjuvant radiation is too aggressive following the initial gross total resection (2)(3)(4)9).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that there is no evidence to support the use of adjuvant radiation in the prevention of recurrence and due to the side-effects of radiation, the majority of studies in the literature recommended a gross total resection, with a focus on quality of life, and a long-term follow-up plan (7)(8)(9). When recurrence was observed, repeat surgery and adjuvant radiation was recommended, as the pathology of the recurrence was always more aggressive than the primary tumor (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the steep dose gradient at the edge of the target volume, the included margin of normal brain tissue can be minimized. This may result in a reduction of treatment-related early or late toxicity [1,9,21,23,27]. In view of the excellent prognosis of NC patients, with reported long-term survival rates of 93-100% [23], a highly conformal radiation technique is required to reduce the risk of late toxicities such as leukoencepahlopathy, cognitive dysfunction, white matter necrosis, intracerebral vasculopathy, or even radiation-induced malignancies [6,15,19,23].…”
Section: Schlüsselwörtermentioning
confidence: 99%
“…1 [1,3,4,7,9,10,13,14,17,21,23,26,28,31]. Most of the reports are small retrospective case series including <10 patients [1,3,4,7,17,28], four papers are single case reports [10,13,21,31], and only three series provided results in >10 patients [9,14,23]. Kim et al [14] presented a series of 13 patients who underwent GKRS as primary treatment approach (n=6) as well as for residual or recurrent disease (n=7).…”
Section: Schlüsselwörtermentioning
confidence: 99%
See 1 more Smart Citation